Penggunaan Metode Storytelling Untuk Mengurangi Perilaku Agresif Anak TK - Wilda Mumtazah; Suci Rahmadani; Dewi Salistina; Fidrayani (JURUSAN PENDIDIKAN GURU PENDIDIKAN ANAK USIA DINI, 2024)
Aggressive behavior is negative behavior or actions both physically and verbally that tend to be dangerous and can even hurt and harm others. Aggressive behavior that occurs among children needs to be addressed as early as possible referring to the nature of early childhood which is an individual who is in the golden age. The purpose of this study was to reduce the aggressive behavior identified in children in Group A of Madania School Kahuripan Kindergarten. The research method used in this study is a class action research method in which there are four stages which include the stages of planning, action, observation, and reflection. Data collection techniques are through interviews, observations, and documentation that refer to the research instruments developed. The results of this study suggest that storytelling methods can be used to reduce children's aggressive behavior. In pre-action, it was found that the decrease in children's aggressive behavior reached a percentage of 47%, then in cycle I it reached 52% and in cycle II it reached 54.5%. This method is effective because the stories used are stories related to the child's condition.